Prevalence and Pattern of Neurological Disorders amongst Children Attending the Neurology Clinic of a Private Paediatric Hospital in Southern Nigeria - , Boma Awoala West; , Josephine Enekole Aitafo (Archives of Current Research International, 2025)
Aim: Neurologic disorders are a common cause of morbidity and disability in children worldwide. There is a dearth of knowledge of neurologic disorders in private health facilities thus this study was done to determine the prevalence and pattern of these disorders. Study Design: It was a retrospective study. Place and Duration of Study: This study was carried out in a private paediatric hospital in Southern Nigeria over 1-year between 1st January, 2023 and 31th December, 2023. Methodology: Data was extracted from the hospital’s health management system and analysed. Results: Of the 22,965 outpatient clinic visits during the study period, 203 had neurological disorders giving a prevalence rate of 0.9% with slight female predominance 107(52.7). Most common age group was 1 - < 5 years (43.4%). Single neurologic disorders predominated 123 (63.4%). Commonest neurological disorders were seizure disorder (54.6%), autism spectrum disorder (24.3%) and attention deficit hyperactive disorder (11.3%) with the commonest risk factors for neurologic disorders being severe perinatal asphyxia (42.1%) and severe neonatal jaundice (42.1%). There were significantly more males than females with seizure disorder (P value .013) whereas cerebral palsy was significantly more in females (P value .002). Seizure disorder and learning disorder were significantly more in children ³ 5years (P value of .001 & .030 respectively) whereas cerebral palsy and speech impairment were significantly more in children < 5years (P value of < .001 & .030 respectively). Conclusion: The prevalence of neurologic disorders was low, being 0.9% with children under 5 years being mostly affected. Commonest neurologic disorders were seizure disorder, autism spectrum disorder and attention deficit hyperactive disorder while perinatal asphyxia and neonatal jaundice were the commonest risk factors. Public enlightenment campaigns about neurologic disorders and the availability of care would improve the outcome of affected children.